(untitled) (Journal of Science and Technology, 2016)
This study sought to establish the prevalence of the metabolic syndrome (MetS) among active sportsmen/sportswomen and sedentary workers in the Kumasi Metropolis using the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III), World Health Organization (WHO), and International Diabetes Federation (IDF) criteria. The study was conducted between March and April, 2010. One hundred and eighty six (186) participants were involved with eighty five (85) being active sportsmen/sportswomen as study control and one hundred and one (101) sedentary workers from the Kumasi metropolis as study subjects. The study participants were recruited from a population of young and adult individuals between the ages of 19-82 years. The percentage prevalence of MetS was 1.6%, 7.4% and 14.4% when the WHO, NCEP-ATP III and IDF criteria respectively were applied on the total population. Generally, the prevalence of MetS was significantly higher among the sedentary group i.e. 3.5%, 14.0% and 26.7% for WHO, NCEP-ATP III and IDF criteria respectively as compared to the active population i.e. 0.0%, 2.0% and 3.9% for WHO, NCEP-ATP III and IDF criteria respectively. The prevalence of the MetS varied greatly between the active and sedentary subjects depending on the criteria used. Central obesity appears to be the key determinant of the prevalence of the MetS in Ghana. Preventive actions such as exercise, active lifestyles and healthy eating habits have to be implemented to reduce the tendency to obesity and MetS in the Ghanaian populace.